Effect of copper substitution on structural, optical and humidity-sensing characteristics of cerium oxide nanoparticles. (January 2020) - Vigneselvan, S.; Manikandan, V.; Petrila, Iulian; Vanitha, A.; Chandrasekaran, J.
Abstract: Cerium (pure) and copper-substituted cerium oxide nanoparticles were synthesized by microwave oven method. Powder X-ray diffraction showed that particle size was reduced with increases in copper content, termed the "particle size effect". Scanning electron microscopy and transmission electron microscopy (TEM) images showed that particle formation was spherical. Miniature sizes of nanoparticles were in the range 4–10 nm and were identified from typical TEM microstructures. Absorption peaks were reduced as result of copper content and binding energy was also reduced, which decreased the particle size. The particle size effect produced significant changes in humidity sensing, copper-substituted cerium oxide nanoparticles had better humidity-sensing behavior than pure cerium oxide. Reproducibility of the sensor produced notable sensing characteristics. Highlights: The fabricated sensors performed well in ideal and real environments. Significant sensitivity was found following the incorporation of copper. Sensors showed good responses in reproducibility testing.